A Practical Approach to Terminological Research in Specialized Translation - Akpaca, Servais Martial (Journal of Ecohumanism, 2024)
This article aims to show translators facing terminological challenges a practical way of overcoming problems related to the search for terms’ and concepts’ meanings. It uses mixed methods. Firstly, it assesses and interprets terms’ meanings in the syntactic contexts in which they are found. Sometimes, some terms have different meanings in different contexts. The search for the meaning of a specific term is carried out in a corpus that shows many occurrences of the term. Secondly, the number of occurrences is counted and the term's meaning in every context is interpreted. By so doing, the translator does the work of a terminologist who defines terms’ meanings (i.e. a micro-definition) and delineates their contours in a specific corpus. The findings of this research include the following: (1) the meaning of a term can be investigated and defined by the translator as a result of a terminological exploration; (2) corpora provide adequate sources for research on lexical semantics; (3) dictionary definitions have limitations and can be complemented or challenged by terminological definitions; (4) meaning is a dynamic notion that evolves with time and in space; (5) a practical approach to lexical semantics is the way forward.